RESEARCH ON FACTORS AFFECTING CUSTOMERS’ INTENTION TO USE ACCOMMODATION SERVICES FOR HOTEL ENTERPRISE IN KIEN GIANG –VIETNAM - Giang, Nguyen Hong; Le, Doan Hong; Trang, Tran Van; Giang, Doan Quynh (The journal of contemporary issues in business and government, 2022)
In Vietnam, there has not been any research on behavior before using products and services - especially in the field of hotel services in the whole country as well as in Kien Giang province. This study builds a theoretical model of the factors affecting the intention to use hotel services of customers based on the theory of spillover of innovation by Rogers (2003) (DIT) and the unified theory of customer satisfaction. technology adoption and use (UTAUT) by Venkatesh et al (2012). On that basis, the authors has built a model of factors affecting the intention to use hotel services of tourists in Kien Giang province, Vietnam, including factors: relative advantage, influence social, facilitation, hedonic motives, values, habits, customer innovation with 600 questionnaires. Combined with empirical investigation, the paper helps hotel businesses in Kien Giang province and in nationwide to better perceive marketing activities and as well as making recommendations to enhance marketing capabilities, and attract more tourists to hotels in next time .